Response of some narbon vetch varieties to different plant populations for growth and yield under two locations of sulaimani region - Abdullah, Avan Rahman; Rafaf, Jwan Gharib (Journal of Kerbala for Agricultural Sciences, 2019)
This study was carried out in Sulaymaniyah governorate at two locations Qlyasan (Lat 35°33´ ; N,Long 45° 21´ ; E,750 MASAL) and Kanipanka (Lat 35° 22´; N Long 45° 43´ ; E,550 MASAL),during the growing season of 2017-2018 to evaluate the response of four Narbon vetch (ICARDA833, ICARDA225, ICARDA776, ICARDA545) varieties, and four plant Density (80Kg,100Kg,120Kg, and 140Kg) and planting date (December 5th )in Kanipanka (December 6th ) Qlyasan.The design of factorial within CRBD experiment with three replications . Means comparison was carried out by the mean of least probability difference (L.S.D) at a significant level of 5%. The results confirmed that variety No. 1(ICARDA833) and variety No.4 produced the highest seed yield and some of its yield components of seeds. Using 140Kg seeds hectar-1 produced the highest seed yield and some of exhibited the highest value for seed yield and some it is components and growth characters. The highest value for seed yield and most it is components produced at Kanipanka location compare to Qlyasan location.